International Economic Projects as a Development Tool of BRICS - Li Jingcheng (Евразийская интеграция: экономика, право, политика, 2019)
This article is devoted to the problems and prospects of economic activity of the BRICS member countries. Analyzing the national programs of Brazil, Russia, India, China and South Africa in the field of international economic activity on the basis of a comparative method, the article provides practical measures to resolve conflicts of interests of the BRICS countries and the development of mutual understanding. The article concludes with a tendency towards the formation of a multipolar system of international relations and the growing interdependence of the BRICS countries, emphasizes the importance of economic integration and financial cooperation between these countries to protect against an unstable external environment and preserve national socio-economic development.